Proton Gradients and Proton-Dependent Transport Processes in the Chloroplast - Höhner, Ricarda; Aboukila, Ali; Kunz, Hans-Henning; Venema, Kees (Frontiers in Plant Science, 2016)
Proton gradients are fundamental to chloroplast function. Across thylakoid membranes, the light induced -proton gradient is essential for ATP synthesis. As a result of proton pumping into the thylakoid lumen, an alkaline stromal pH develops, which is required for full activation of pH-dependent Calvin Benson cycle enzymes. This implies that a pH gradient between the cytosol (pH 7) and the stroma (pH 8) is established upon illumination. To maintain this pH gradient chloroplasts actively extrude protons. More than 30 years ago it was already established that these proton fluxes are electrically counterbalanced by Mg2+, K+, or Cl- fluxes, but only recently the first transport systems that regulate the pH gradient were identified. Notably several (Na+,K+)/H+ antiporter systems where identified, that play a role in pH gradient regulation, ion homeostasis, osmoregulation, or coupling of secondary active transport. The established pH gradients are important to drive uptake of essential ions and solutes, but not many transporters involved have been identified to date. In this mini review we summarize the current status in the field and the open questions that need to be addressed in order to understand how pH gradients are maintained, how this is interconnected with other transport processes and what this means for chloroplast function.